The science of science: Clinical Science launches a new translational meta-research collection. Issue 16 (27th August 2021) - Weissgerber, Tracey L.
Abstract: Clinical Science is proud to launch a new translational meta-research collection. Meta-research, or the science of science, applies the scientific method to study science itself. Meta-research is a powerful tool for identifying common problems in scientific papers, assessing their impact, and testing solutions to improve the transparency, rigor, trustworthiness, and usefulness of biomedical research. The collection welcomes science of science studies that link basic science to disease mechanisms, as well as meta-research articles highlighting opportunities to improve transparency, rigor, and reproducibility among the types of papers published in Clinical Science . Submissions might include science of science studies that explore factors linked to successful translation, or meta-research on experimental methods or study designs that are often used in translational research. We hope that this collection will encourage scientists to think critically about current practices and take advantage of opportunities to make their own research more transparent, rigorous, and reproducible.